Developing informational text writing skills of gifted students by leveraging writing strategies - Erbasan, Ömer; Dedeoğlu, Hakan (Afyon Kocatepe Üniversitesi)
Designed as action research, this qualitative study aims to develop the informational text writing skills of gifted students through the strategies of “all about” books and “biography writing frames”. The study group of the research consists of 21 gifted 4th-grade students studying in the field of general mental ability in a Science and Art Center in the spring semester of the 2020-2021 academic year. An eight-week action plan was prepared to support the development of these students’ ability to write informational texts. The first 4 weeks were planned with the strategy of “all about” books, and the last 4 weeks with the strategy of biography writing frames. The data were collected with student and teacher diaries, observer reports, and student products were scored through Informational Text Writing Rubric. Content analysis was used for the analysis of the collected data. The analysis of the data revealed that while the informational text writing skills of the students were at a moderate level at the beginning, they reached a high level at the end of the process. Based on the findings, some suggestions were presented to teachers and researchers to improve students’ ability to write informational texts.

Bu araştırmada “işimiz gücümüz kitaplar ve “biyografi yazma çerçeveleri” stratejileriyle özel yetenekli öğrencilerin bilgilendirici metin yazma becerilerinin geliştirilmesi amaçlanmıştır. Araştırma eylem araştırması deseni ile yürütülmüştür. Araştırmanın çalışma grubunu, 2020-2021 eğitim öğretim yılının bahar döneminde bir Bilim ve Sanat Merkezinde genel zihinsel yetenek alanında eğitim gören 21 özel yetenekli 4. sınıf öğrencisi oluşturmaktadır. Bu öğrencilerin bilgilendirici metin yazma becerilerinin gelişimini desteklemek için sekiz haftalık bir eylem planı hazırlanmıştır. İlk 4 hafta işimiz gücümüz kitaplar, son 4 hafta biyografi yazma çerçeveleri stratejileri ile planlanmıştır. Araştırmanın verileri öğrenci-öğretmen günlükleri ve gözlemci raporları ile toplanmış, öğrencilerin yazdığı metinler “Bilgilendirici Metin Yazma Dereceli Puanlama Anahtarı” ile puanlanmıştır. Toplanan verilerin analizinde içerik analizi kullanılmıştır. Araştırmada öğrencilerin bilgilendirici metin yazma becerilerinin başlangıçta orta düzeydeyken sürecin sonunda yüksek düzeye ulaştığı belirlenmiştir. Araştırma sonuçlarına dayanarak öğrencilerin bilgilendirici metin yazma becerisini geliştirmeye dönük öğretmenlere ve araştırmacılara bazı öneriler sunulmuştur.
Yazma stratejileri ile özel yetenekli öğrencilerin bilgilendirici metin yazma becerilerinin geliştirilmesi
Keywords: Writing Skills; All About Books; Frames for Writing Biographies; Gifted Students; Yazma Becerileri; İşimiz Gücümüz Kitaplar; Biyografi Yazma Çerçeveleri; Özel Yetenekli Öğrenciler; Bilgilendirici Metin Yazma